Surveying Caribbean Cultural Landscapes: Mount Plantation, Barbados, and its global connections - Jonathan Finch; Douglas Armstrong; Edward Blinkhorn; David Barker (Internet Archaeology, 2013)
The first systematic archaeological investigation on Barbados since the 1970s at Mount Plantation, St George, Barbados, has yielded significant material and landscape data relating to world-changing economic and social structures, from the dramatic early 18th-century escalation of slavery to the agro-industrial production in the British Caribbean during the late 19th century. This article focuses on two related research aims. It offers the evaluation of systematic archaeological fieldwork which combines geophysical survey techniques and fieldwalking in the British Caribbean, thus offering the first results from a methodology for rapidly assessing the archaeological potential of plantation sites. Secondly, it systematically characterises the plough-zone archaeology on a Barbadian plantation. The site provides an example of shifts in plantation organisation and labour over the 18th and early 19th centuries, and forms an integral element within the study of created and transformed landscapes owned by the Lascelles family in Barbados and Yorkshire (UK), thus connecting Caribbean cultural landscapes directly with those in Britain.